Dietary Thymol Improved Growth, Body Composition, Digestive Enzyme Activities, Hematology, Immunity, Antioxidant Defense, and Resistance to Streptococcus iniae in the Rainbow Trout (Oncorhynchus mykiss) - Hafsan Hafsan; Marwan Mahmood Saleh; Rahman S. Zabibah; Rasha Fadhel Obaid; Hijran Sanaan Jabbar; Yasser Fakri Mustafa; Mohammed Q. Sultan; Gamal A. Gabr; Andrés Alexis Ramírez-Coronel; Mohammad Khodadadi; Mahnaz Dadras (Aquaculture Nutrition)
In this study, thymol (TYM) at dietary levels of 0, 1, 1.5, 2, and 2.5 g/kg diet was used to evaluate its effects on growth, digestive performance, immunity, and resistances to the infection induced by Streptococcus iniae in the rainbow trout, Oncorhynchus mykiss. A number of 450 fish (35.8±4.4 g; Mean±SD) were distributed to 15 tanks (30 fish/tank) in three replicates and fed TYM for 60 days. After feeding period, Fish fed 1.5-2.5 g TYM showed better growth, higher digestive enzyme activity, and body protein content compared to other diets (P<0.05). Regression analysis indicated a polynomial relationship between growth parameters and dietary TYM levels. Based upon the varied growth parameters, the optimum dietary TYM level was 1.89% for FCR. TYM at dietary levels of 1.5-2.5 g significantly enhanced liver antioxidant enzyme activity [superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase (CAT)], immune components in blood [alternative complement activity (C3), total immunoglobulin (Ig), lysozyme activity, bactericidal activity, and total protein], and in mucus [alkaline phosphatase (ALP), protease activity, lysozyme activity, bactericidal activity, and total protein] compared to other diets (P<0.05). TYM at dietary levels of 2-2.5 g significantly decreased malondialdehyde (MDA) levels compared to other experimental groups (P<0.05). In addition, use of TYM at dietary levels of 1.5-2.5 g upregulated the expression of the immune-related genes (C3, Lyz, and Ig) (P<0.05). In contrast, the expression of inflammatory genes, tumor necrosis factor (TNF-α) and Interleukin-8 (IL-8) significantly were downregulated in response to 2-2.5 g TYM (P<0.05). The hematology of the fish also altered in response to dietary TYM, where the values of corpuscular hemoglobin concentration (MCHC), hemoglobin (Hb), red blood cell (RBC), hematocrit (Hct), and white blood cell (WBC) significantly increased in fish fed 2-2.5 g TYM compared to other diets (P<0.05). In addition, MCV significantly decreased in response to 2-2.5 g TYM (P<0.05). After challenge with Streptococcus iniae, the survival rate was significantly higher in fish fed 2-2.5 g TYM compared to other diets (P<0.05). The results of the present study concluded that TYM in the diet of rainbow trout can improve the fish growth and immunity and increase the resistance of the fish to Streptococcus iniae infection. The results of this study recommend an optimized dietary level of 2-2.5 g TYM for the fish.